IDNLearn.com makes it easy to find answers and share knowledge with others. Get comprehensive answers to all your questions from our network of experienced experts.
Sagot :
Answer:
x = [tex]-\frac{4}{3}[/tex]
Step-by-step explanation:
Distributive Property:
3 (x - 4) = 12x
3x - 12 = 12x
Combine like terms and isolate the variable:
3x - 12 = 12x
-12 = 9x
[tex]-\frac{4}{3}[/tex] = x
x = [tex]-\frac{4}{3}[/tex]
Answer:
x = [tex]\frac{-4}{3}[/tex]
Step-by-step explanation:
3(x - 4) = 12x
3x - 12 = 12x --->by the distributive property of equality
-9x = 12 ---> subtraction property of equality
x = -9/12 ---> division property of equality
x = -4/3 as simplified
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is committed to your satisfaction. Thank you for visiting, and see you next time for more helpful answers.